Microstructure-dependent phosphating film formation and its corrosion behavior in AZ91 Mg alloy: Effect of extrusion temperature - Haolong Bai; Junlei Zhang; Qiuyue Shi; Xiang Chen; Xuwen Yuan; Shengbo Hu; Chao He; Qi Zhao; Shuping Tan; Yifu Shen; Guangsheng Huang (Journal of Materials Research and Technology)
In this study, the extrusion temperature (350–450 °C)-dependent microstructure evolution of AZ91 Mg alloy and its effects on the formation mechanisms of phosphate film and corrosion behavior were systematically analyzed. Results revealed that extrusion at 350 °C resulted in a refined microstructure with an average grain size of 8.9 μm, accompanied by an intensified basal texture (mud = 18.20) and a high proportion (64.8 %) of basal-oriented grains compared to 400 °C and 450 °C processed counterparts. The refined grain size accelerated phosphate nucleation kinetics, while the intensified basal texture and enhanced basal-oriented grain fraction promoted epitaxial growth of a dense composite film layer of MgHPO4, Al(OH)3, and MnHPO4 with an average thickness of 27 ± 2.0 μm, thereby exhibiting the lowest absolute value of corrosion current density (3.91 × 10−6 A/cm2) and superior salt spray resistance. Conversely, high-temperature extrusion (450 °C) induced grain coarsening (14.7 μm) and texture randomization (27.2.0 % basal-oriented grains), which led to a relatively thin and less uniform phosphate film with increased microcracks, thereby compromising the corrosion performance. Additionally, the precipitate evolution exhibited a non-monotonic temperature dependence, peaking at 400 °C (2.1 ± 0.45 % area fraction), but its influence diminished as the phosphating film fully developed. Additionally, the dislocation density exhibited a negligible influence on film formation and corrosion resistance. The current research offers insights into achieving phosphating film with excellent corrosion resistance through microstructural design controlled by extrusion temperature.